Comparison and assessment of a different steel materials based on core losses reduction for three-phase induction motor - Yaser Atta Yassin; Ali Nasser Hussain; Nagham Yassin Ahmed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper presents a core losses and performance calculation with different type of steel materials in the core design for three-phase induction motor by using "ANSYS Maxwell" program in order to identify the core material that provides the most effective performance by iron losses reduction. The coefficients of core losses are calculated from the magnetization curve and core Loss curve based on the on steel material databases. Although the difficult to obtain because of the little of existing information. Results show the capability of the proposed Cobalt steel (Hiperco 50) to achieve the significant losses reduction in comparison to the Electrical Steel NGO–AK Steel’s M-19 and Low Carbon Steel-SAE1020.